THE EXPERIMENTAL DETERMINATION METHODOLOGY OF THE PARAMETERS IN THE EQUATION OF THE AIR TEMPERATURE DISTRIBUTION ON THE HFS HEIGHT - V. G. Gagarin; N. Yu. Plyushchenko; A. R. Kosarev (Вестник СибАДИ)
The research of the HPS effectiveness and the area of their application because of the wide application in the construction of hinged facade systems  (NFS) with a ventilated air interlayer is actual nowadays. The fullscale experimental study of the temperature change in the facade height  in the summer period is carried out. The differential equation for the  distribution of temperature along the interlayer height is used for the process of the experimental data. To simplify the processing of the  experimental data, in this differential equation the variability is made. The  equation contains two parameters, which depend on the temperature of the  outside  solution. The equation is represented in finite differences and by  means of such equation the determination of the parameters of the equation  from the experimental data is obtained. The calculation of the differential equation with the found parameters is presented. The calculations from the  obtained equation are compared with the experimental data. The comparative analysis shows an acceptable error between calculated and experimental data. The developed technique for the equation parameters’  determination makes it possible to find the numerical values of the air gap  characteristics, which would increase the calculations’ accuracy for the operational HFS parameters’ determination in their thermal performance.